Effects of Polycystic Ovary Syndrome (PCOS), Sex Hormones, and Obesity on Circulating miRNA-21, miRNA-27b, miRNA-103, and miRNA-155 Expression - Murri, Mora; Insenser, María; Fernández-Durán, Elena; San-Millán, José L.; Escobar-Morreale, Héctor F. (The journal of clinical endocrinology and metabolism, 2013)
Context:MicroRNAs (miRNAs) are small, noncoding RNA sequences that negatively regulate gene expression at the post-transcriptional level. miRNA-21, miRNA-27b, miRNA-103, and miRNA-155 have been associated with metabolic disorders such as obesity and diabetes, which are also associated with polycystic ovary syndrome (PCOS).Objective:We aimed to evaluate the effects of sex, sex hormones, and PCOS and their interactions with obesity on the expression in the circulation of these miRNAs.Design:This was a case-control study.Settings:The setting was an academic hospital.Participants:We included 12 control women, 12 patients with PCOS, and 12 men selected as to have similar body mass index (BMI) and age. Six subjects per group had normal weight (BMI < 25 kg/m2), and six subjects per group were obese (BMI ≥ 30 kg/m2).Interventions:Blood samples were collected early in the morning after a 12-hour fast.Main Outcome Measures:We measured whole blood expression of miRNA-21, miRNA-27b, miRNA-103, and miRNA-155.Results:Obesity significantly reduced the expression of miRNA-21, miRNA-27b, and miRNA-103. However, there was a significant interaction between obesity and the group of subjects in the expression of miRNA-21, miRNA-27b, miRNA-103, and miRNA-155 consisting of obesity reducing the expression of these miRNAs in control woman and men, but tending to increase their expression in women with PCOS. These differences paralleled those observed in serum T concentrations.Conclusions:The present results suggest that miRNAs that play an important role in metabolic and immune system processes are influenced by obesity and circulating androgen concentrations.